IMPLEMENTATION OF REGULATION OF THE MINISTER OF HEALTH OF THE REPUBLIC OF INDONESIA NUMBER 24 OF 2022 CONCERNING ELECTRONIC MEDICAL RECORDS STUDY AT THE UPTD OF THE SPECIAL LUNG HOSPITAL OF NORTH SUMATRA PROVINCE (International Journal of Cultural and Social Science, 2026)
The implementation of Electronic Medical Records (EMR) is a strategic policy of the Ministry of Health of the Republic of Indonesia, based on Ministerial Regulation Number 24 of 2022, which mandates that all healthcare facilities, including the Lung Specialist Hospital Technical Implementation Unit (UPTD), be implemented optimally. This study aims to analyze the implementation of Ministerial Regulation Number 24 of 2022 concerning Electronic Medical Records at the UPTD Lung Specialist Hospital in North Sumatra Province and identify the inhibiting factors in its implementation. This study used qualitative methods and analyzed policy implementation using George C. Edward III's theory, which encompasses aspects of communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of Ministerial Regulation Number 24 of 2022 concerning Electronic Medical Records at the UPTD Lung Specialist Hospital in North Sumatra Province has progressed well in stages, but still faces various challenges. Research suggestions include the need to increase human resource capacity through intensive and continuous training for health workers and administrative staff so that they are better prepared and skilled in operating the Electronic Medical Record system.